HUBUNGAN STIMULASI PERKEMBANGAN DENGAN SOCIAL SKILL ANAK USIA 4-5 TAHUN DI TK QUSHRUL UBUDIYAH - Adelia Septania Widyanti; Annisa Wigati Rozifa; A'im Matun Nadhiroh (LPPM Universitas Abdurrab, 2024)
Background: A development of children's social skills can be seen at the age of 4-5 years. The problems that arise at this stage are conflicts with friends, passivity, fear of doing something, lack of willingness to learn. The low social skills can cause children to be less able to establish relationships with others, tend to have unpleasant relationships and get negative feedback. This research on children aged 4-5 years states that children’s social skill was low by 28%. Objective: to determine the relationship between developmental stimulation and social skills of children aged 4-5 years in Kindergarten of Qushrul Ubudiyah, Working Area of Health Center in Jagir of Surabaya City. Research methods: survey and observational with cross sectional design. The research location is in Kindergarten of Qusrul Ubudiyah in Working Area of Health Center in Jagir of Surabaya. The subjects were mothers and children aged 4-5 years. The number of samples was 32 people that used simple random sampling technique. The child's social skills were observed three times, then the average value was taken, while the stimulation directly asked the mother via a questionnaire. The data analysis was carried out through two stages, namely univariate and bivariate analysis with a level of significance (p<0.05) and a CI of 95%. The results: in general, developmental stimulation was high, and social skill was good, developmental stimulation was related to children’s social skill. The higher the developmental stimulation, the better the children’s social skills marked by (r = 0.389, p < 0.05). Conclusion: The higher the developmental stimulation that was the better the children’s social skills. It is hoped that all family members work together to provide stimulation and it is not just the responsibility of the mother